2020
DOI: 10.3389/fbioe.2020.576348
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineered Metal-Organic Frameworks (MOFs) Based Novel Hybrid Systems for Effective Wound Healing: A Review of Recent Developments

Abstract: Wounds present serious medical complications and their healing requires strategies that promote angiogenesis, deposition of collagen as well as re-epithelialization of wounds. Currently used conventional wound healing strategies have become less effective due to various issues associated with them. Thus, novel strategies are needed to be developed for early and effective healing of wounds. Metal-organic frameworks (MOFs), formed by linking of metal ions through organic bridging ligands, are highly tunable hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 74 publications
(114 reference statements)
0
12
0
Order By: Relevance
“…193 Due to the bactericidal ability of metal ions such as Ag + , Zn 2+ , and Cu 2+ , NNPHs with MOF-based nanomaterials serving as nanofillers have also been studied for wound healing applications. 194–196 Deng et al reported an injectable biomimetic NNPH using metal–organic frameworks (MOFs) with encapsulated Au nanoparticles (Au@ZIF-8) and hydrogels prepared using carbohydrazide-modified GelMa and oxidized sodium alginate through a Schiff-base as well as photo crosslinking. The NNPH displayed photodynamic bactericidal performance, with >99.0% of bacteria eradicated after light exposure (generating ROS) for 20 minutes.…”
Section: Preparation and Performance Of Nnphs According To Their Nano...mentioning
confidence: 99%
“…193 Due to the bactericidal ability of metal ions such as Ag + , Zn 2+ , and Cu 2+ , NNPHs with MOF-based nanomaterials serving as nanofillers have also been studied for wound healing applications. 194–196 Deng et al reported an injectable biomimetic NNPH using metal–organic frameworks (MOFs) with encapsulated Au nanoparticles (Au@ZIF-8) and hydrogels prepared using carbohydrazide-modified GelMa and oxidized sodium alginate through a Schiff-base as well as photo crosslinking. The NNPH displayed photodynamic bactericidal performance, with >99.0% of bacteria eradicated after light exposure (generating ROS) for 20 minutes.…”
Section: Preparation and Performance Of Nnphs According To Their Nano...mentioning
confidence: 99%
“…In addition, myofibroblast highly expresses cytoskeleton α-actin, a type of smooth muscle protein that is essential for the contraction of the blood vessel [ 38 ]. At the final stage of wound healing, the myofibroblasts will be destroyed while cross-linked collagen fibers are rearranged and regulated by growth factors to give the newly formed scar a better tensile strength [ 39 ]. Table 1 shows the difference between acute and chronic wounds.…”
Section: Skin Wound Healingmentioning
confidence: 99%
“…22,23 Therefore, bone materials must have anti-corrosion and anti-infection properties. 22 MOFs contain metal ions, and based on the unique structure of MOFs, metal ions in the central structure can be released as needed, which can not only play an anti-bacterial and anti-infection role and promote wound healing, 22,24,25 but also enhance the ALP activity and play an important role in the process of osteogenesis. 22,24 Also, the ideal biological skeletal material needs to be capable of transporting materials, thus preventing bone loss.…”
Section: Introductionmentioning
confidence: 99%